Efektivitas Eco Art Therapy untuk Mereduksi Perilaku Prokrastinasi Akademik pada Siswa Kelas XI SMAN 1 Leuwiliang - Triana Agustin; Ahmad Waki; Nurodin Nurodin (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
Academic procrastination is a common problem among students as it leads to delays in completing academic tasks and poor time management. This study aimed to determine the effectiveness of eco art therapy in reducing academic procrastination among eleventh-grade students at SMAN 1 Leuwiliang. This study employed a quantitative method using a pre-experimental one group pretest-posttest design. The participants consisted of six students selected through purposive sampling based on the highest academic procrastination scores. Data were collected using a valid and reliable academic procrastination scale questionnaire and analyzed descriptively by comparing the pre-test and post-test results. The results showed that the average academic procrastination score decreased from 95.00 (79%) in the pre-test to 83.33 in the post-test, representing a 12% reduction. These findings indicate that eco art therapy is effective as an alternative guidance and counseling service to reduce students' academic procrastination.